(untitled) (Journal of the College of Basic Education, 2024)
This study aims to evaluate digital proficiency of geography teachers in secondary schools within the Diyala province, particularly focusing on their competence in virtual learning environments. The Statistical Package for the Social Sciences (SPSS) will be employed to collect and analyse primary data through the survey-field research approach. A sample of 98 instructors and schools has been selected from the overall research population of 693 teachers and schools, specifically encompassing geography teachers at government secondary schools in the Diyala, The level of digital proficiency among secondary school geography teachers in online learning settings was gauged using a 25-item questionnaire, whose validity and reliability were confirmed by experts in the field. The study’s results, with a significance level of (0.05), indicate a statistically significant connection between all questionnaire items and the three when both genders were combined and categorized by experience (less than 10 years and greater than 10 years). Additionally, both genders combined (less than 10 years) (greater than 10 years), female geography teachers exhibited higher arithmetic means than their male counterparts in the gender variable. Geography teachers with less than 10 years of experience demonstrated a notable deficiency in digital competencies with virtual learning environments. The findings underscore a substantial lack of digital proficiency among secondary school geography teachers in virtual learning environments. Recommendations from the researcher include initiatives to educate geography instructors on digital tools and researches, enhancing their digital literacy for applications in secondary schools’ virtual learning environments. The researcher also emphasizes the need to focus on educating female geography instructors on effectively utilizing these technological tools and resources in the teaching and learning process. Additionally, the researcher suggests conducting a study to advance the digital proficiency of secondary school geography teachers in online learning settings.